Potentiating the activity of berberine for Staphylococcus aureus in a combinatorial treatment with thymol - SARIYAR AKBULUT, BERNA; SAYAR, NİHAT ALPAGU (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2020)
A plethora of natural products emerges as attractive molecules in the struggle against antibiotic resistance. These molecules impose their bioactivities not only alone but also in combinations as well, which further enhances their effects. Berberine is a well-known isoquinoline alkaloid with antibacterial activity. Unfortunately, it is readily extruded, which significantly reduces its efficacy and restricts its potential. Thymol is a monoterpenic phenol that exhibits different biological activities but its major effect is observed only at relatively high concentrations, which raises concern on cytotoxicity. The aim of the study was to potentiate the antibacterial activity of berberine, in a combination treatment with thymol in the opportunistic pathogen Staphylococcus aureus and understand the antibacterial mechanism of the combination treatment. The synergism of berberine and thymol was first established by the checkerboard assay. Then the antibacterial mechanism of the synergistic combination was explored by growth curves, biofilm formation assay, SEM observation, and RNA-Seq based transcriptomic profiling. Checkerboard assay showed that 32 mu g mL(-1) berberine and 64 mu g mL(-1) thymol was a synergistic combination, both concentrations below their cytotoxicity limits for many cells. 32 mu g mL(-1) berberine and 32 mu g mL(-1) thymol was sufficient to inhibit biofilm formation. SEM images confirmed the morphological changes on the structure of combination treated cells. The major finding of the combination treatment from the transcriptomic analysis was the repression in the expression of virulence factors or genes related to virulence factors. Apart from the particular changes related to the cell envelope, the majority of expressional changes seemed to be similar to berberine-treated cells or to be resulting from general stress conditions. The findings of this work showed that when thymol was used in combination with berberine, it enhanced the antibacterial activity of berberine in a synergistic manner. Furthermore, thymol could be considered as an antivirulence agent, disarming S. aureus cells.
Keywords: Staphylococcus aureus; Thymol; Berberine; Synergistic effect; Antivirulence; ANTIBACTERIAL MECHANISM; ESCHERICHIA-COLI; CARVACROL; RESISTANCE; EXPRESSION; ANTIBIOTICS; COMPETENCE; APOPTOSIS; EUGENOL; SYNERGY